A CASE SERIES OF POTENTIAL CONSEQUENCES FOLLOWING INTRAMUSCULAR INJECTIONS IN CHILDREN - Sidek, Ruzihan; Ambak, Noor Azleen; Alias, Mazni; Tamrin, Noor Fariza Mohammed; Samingan, Nurshadia; Leong, Annie; Yaakop, Siti Zarina; Jalaludin, Muhammad Yazid; Zaini, Azriyanti Anuar (Journal of the ASEAN Federation of Endocrine Societies, 2025)
INTRODUCTION Apart from regular vaccinations, there are limited instances where deep intramuscular (IM) injections are given to children. I.M gonadotropin agonist (GnRHa) is used for the treatment of central precocious puberty (CPP). It is given deep IM at the upper outer quadrant of the buttock. We describe three cases to demonstrate complications of this procedure. CASE Case 1. An 8-year-old female was diagnosed with CPP at the age of 5 when she presented with breast development. She has been receiving 3-monthly IM GnRHa since then. In the clinic, parents informed that she had a 1-week history of upper respiratory tract infection. She was afebrile and was given an injection as usual. Patient came back a week later complaining of pain and swelling at injection site. After inspection, a diagnosis of sterile abscess was made. She was treated with local and oral antibiotics. Case 2. An 8-year-3-month-old female was diagnosed with CPP at the age of 7 years and 5 months. She was due for her 3rd i.m GnRHa. She has been anxious about injection pain and needed comfort from parents/nurses at each visit. She insisted on more pain relief prophylaxis. She came back after 1 week with circular erythematous rash and blister formation around injection site. Diagnosis of superficial burn secondary to ethylchloride spray was made. Case 3. An 8-year-old female with underlying mild autism was started on GnRHa injections for CPP. At every clinic visit, she will cry, shout and throw tantrums which were attributed to injection anxiety. Parents and nurses had a lot of difficulty getting her ready for injections. On her last visit, the nurse who gave her the injection reported bite marks and bruises on her arm because the patient bit her. CONCLUSION Although rare, one should always take extra precautions when dealing with IM injections in children. Repeated procedures carry higher risk as mentioned in this case series.